A THE EFFECT OF PHYSICAL FITNESS EXERCISE ON GROSS MOTOR SKILLS OF CHILDREN AGED 5-6 YEARS AT DARMAWANITA KINDERGARTEN IN JANTHO CITY - Ramli, Selvia; Faridy, Faizatul; Juwita, Rani Puspa (Universitas Al-Hikmah Indonesia, 2024)
Exercises aimed at improving physical fitness are crucial for kids' gross motor skill development. The gross motor movements of children aged 5 to 6 were found to be relatively low based on observations made at the Darma Wanita Kindergarten in Jantho City. This was due to the children's inability to practice body movements that connect large muscles to themselves or to train gross motor skills. The purpose of this study is to determine the impact of physical fitness activities on the gross motor skills of children enrolled in the Darma Wanita Kindergarten in Jantho City who are between the ages of five and six.